2016
DOI: 10.1080/15412555.2016.1177007
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Ventilatory Parameters, Dynamic Hyperinflation, and Performance in the Glittre-ADL Test in COPD Patients

Abstract: The TGlittre time and ventilatory parameters are reproducible, while DH is variable in COPD patients. A 6-7% learning effect was shown, and it is recommended to perform two tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…26 The reliability and learning effect of TGlittre had also been investigated in previous studies, which demonstrated results similar to ours (ICC 0.95---0.97; learning effect: 6.3---7.6%). 10,12,13 Meanwhile, our study was the first to demonstrate that the learning effect of TGlittre after PRP was about 40% lower than the baseline learning effect. In other words, to perform only one test can overestimate the effects of PRP.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…26 The reliability and learning effect of TGlittre had also been investigated in previous studies, which demonstrated results similar to ours (ICC 0.95---0.97; learning effect: 6.3---7.6%). 10,12,13 Meanwhile, our study was the first to demonstrate that the learning effect of TGlittre after PRP was about 40% lower than the baseline learning effect. In other words, to perform only one test can overestimate the effects of PRP.…”
Section: Discussionmentioning
confidence: 56%
“…In this context, there is the Glittre ADL-test (TGlittre), which is composed by multiple tasks common in daily life, developed, and validated specifically for patients with COPD. 10,11 It is valid 10 and reliable for assessing the functional capacity of clinically stable patients 10,12,13 and hospitalized patients. 14 TGlittre is responsive to PRP 10 and it is able to differentiate the functional capacity of patients with COPD from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Performing a second test gives patients the opportunity to be familiar with the task, and feeling more secure may lead to improved performance. This behavior is common in other functional tests, 11,13 such as the 6-min walk test, in which patients with a greater dyspnea in the first test are better able to control it, reducing this sensation on the second test and being more likely to improve performance. 32 Although only a trend of correlation was found between the number of steps on the 6MST 1 and its variation on the 6MST 2 in the total sample, the Bland-Altman plot (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Studies that aimed to evaluate reproducibility of other functional tests, such as the 6MWT and the Glittre ADL-test, verified a mean percentage difference in performance similar to what we noted in this study, suggesting the presence of a learning effect and therefore the value in performing 2 tests. 11,26 We also identified that the mean difference between 6MST 2 and 6MST 1 was below the MDC and that only 5 subjects showed a difference above the MDC. Given that the MDC reflects the smallest change in the outcome of the instrument that can be considered as a real difference, 24,27 the reliability and responsiveness of the instrument would be compromised if the mean of the difference exceeded MDC.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation